Designing a paradigm model of employees’ voice in organizations providing medical services (a case study: Al-Zahraa Teaching Hospital in Iraq) - Hazim Rebh Najm Al Ghunaimi; Ali Nasr Isfahani; Ali Safari (Journal of Education and Health Promotion)
Background: Al-Zahraa Teaching Hospital, one of the most important hospitals in Iraq, is currently facing extensive organizational problems. One reason for these problems is the lack of attention to the voice of the employees, which can be due to a lack of designing an appropriate model for this phenomenon. Materials and Methods: Accordingly, the present interpretive, qualitative, and exploratory research mainly aimed at designing a voice pattern for the employees in Al-Zahraa Teaching Hospital in Iraq. The field data were analyzed using the grounded data analysis method in the ATLAS.ti 8 software. The research experts included 17 academic experts, managers, and medical, health, and nursing staff of Al-Zahraa Teaching Hospital in Iraq, who were selected by the purposive sampling method. The sample size was determined based on the data saturation method. Result: The research results revealed that the voice of employees can provide managers with a thorough and multi-dimensional understanding of the organization’s situation. Conclusion: Based on the findings of the present study, individual and organizational characteristics are the elements that affect the voice of employees.